Feasibility Assessment of a Sustainable Building Applied Photovoltaic (BAPV) System With Solar Tracking Features Based on Techno-Economic Criteria: Malaysia Case Study - Farah Ramadhani; Oon Erixno; Nasrudin Abd Rahim; Ahmad Rivai; Norridah Amin (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
In line with the increase attention regarding building applied photovoltaic system, the research in enhancing its performance is also critical to be explored, one of them is the utilization of solar tracking system. The goal of this paper is to analyze the feasibility of using a tracking system for increasing the PV output power and analyzing the energy sustainability aspects on a building applied photovoltaic system. A feasibility study considering three scenarios of PV capacities and propose two options in either renewing or reusing the PV panels to extend its life time. Based on the results, the tracking system contributes to the improvement of 18% in the energy generation. On the technical aspects, renewing the PV panels with a large capacity of up to 30 kW-peak is the most feasible option to meet the electricity demand on the building. In the meantime, the reuse option with large capacity is the best with the net present value is about USD 24,639.22 or 34% more than the option of renewal the PV panels. In summary, reusing the panel is beneficial from the economic and environment standpoints as it represents sustainable development of power generation. Since the realistic feasibility cases and analyses used, the novelty in terms of the approach is beneficial for the future investigations on adding a tracking system, keeping or replacing the PV system for sustainable aspect while improving its output power.